1997
DOI: 10.1021/jo970599u
|View full text |Cite
|
Sign up to set email alerts
|

Scandium(III) Triflate-Catalyzed Friedel−Crafts Alkylation Reactions

Abstract: The Sc(OTf)3-catalyzed Friedel−Crafts alkylation reaction with an alcohol, an arenecarbaldehyde or an arenecarbaldehyde acetal as the alkylating agent affords a diarylmethane or an allylbenzene derivative highly selectively. The salient feature of this reaction is that only a catalytic amount of Sc(OTf)3 can effect the reaction. Furthermore, Sc(OTf)3 is recoverable and reusable after the synthetic reaction. The Sc(OTf)3-catalyzed benzylation using an arenecarbaldehyde and 1,3-propanediol or their acetal afford… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
82
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(83 citation statements)
references
References 36 publications
0
82
0
1
Order By: Relevance
“…We observed that all NHC containing complexes of the type [IrCp*A C H T U N G T R E N N U N G (OTf) 2 A C H T U N G T R E N N U N G (NHC)] showed a higher activity than that shown by [{IrCp*Cl 2 …”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…We observed that all NHC containing complexes of the type [IrCp*A C H T U N G T R E N N U N G (OTf) 2 A C H T U N G T R E N N U N G (NHC)] showed a higher activity than that shown by [{IrCp*Cl 2 …”
Section: Resultsmentioning
confidence: 91%
“…In first place, we studied the different activities of several Ir-Cp* complexes (1)(2)(3) in the benzylation of toluene using benzyl alcohols (Table 1). We observed that all NHC containing complexes of the type [IrCp*A C H T U N G T R E N N U N G (OTf) 2 A C H T U N G T R E N N U N G (NHC)] showed a higher activity than that shown by [{IrCp*Cl 2 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] However, these studies did not include a reductive monoalkylation of benzenes with aliphatic aldehydes. In this context, we found that when an aromatic compound was used as a solvent in the reductive iodination of carboxylic acids, unexpected monoalkylated aromatic com-1 ane (TMDS), and molecular iodine.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Considerable progress has been made in the metal-catalyzed Friedel-Crafts alkylation of arenes to generate products containing a diarylmethane moiety commonly found in biologically active compounds. In addition to reports on lanthanide triflate catalysts, [13][14][15][16] Beller and co-workers demonstrated that late transition metal salts such as RhCl 3 , IrCl 3 , H 2 PdCl 4 , H 2 PtCl 6 and HAuCl 4 effectively catalyze the addition of benzyl acetates and benzyl alcohols to arenes. [17,18] Due to the high catalyst loading (5-10 mol %) and expenses of the late transition metals employed, this group recently disclosed an excellent iron-catalyzed benzylation of arenes.…”
mentioning
confidence: 96%